Etudes Physiques et Chimiques sur la Glace de l'Indlandsis du Groenland 1959. - Renaud, A. (Meddelelser om Grønland, 1969)
During the summer campaign of E.G.I.G. 1959 samples have been collected at six stations down to a depth of 1500 cm of water equivalent in a region between 32- 48° West and 69-72° North. The ratios of the isotopes deuterium to hydrogen and oxygen-1 8 to oxygen-16 of the samples as well as their tritium content have been determined. For the first time lead-210 was found in the polar icecaps. Beside the isotopic ratios the composition of the gases extracted from samples of the region of ablation were analysed. Futhermore all samples were studied morphologically.